Handgrip strength is an independent predictor of all-cause mortality in maintenance dialysis patients. Issue 6 (December 2016) - Vogt, Barbara Perez; Borges, Mariana Clementoni Costa; Goés, Cassiana Regina de; Caramori, Jacqueline Costa Teixeira
Summary: Background & aims: Muscle wasting is associated with mortality in dialysis patients. The measurement of muscle mass has some limitations, while muscle strength assessment is simple, safe and allows the recognition of patients at risk of progressing to poor outcomes related to malnutrition. The aim of this study is verify if handgrip strength (HGS) is associated with all-cause mortality in patients in maintenance haemodialysis (HD) and peritoneal dialysis (PD). Methods: This was an observational retrospective cohort study which included all patients in maintenance HD and PD from July 2012 to October 2014. Patients were followed-up until June 2015. Results: Two-hundred sixty five patients were enrolled (218 HD and 47 PD) and they were followed for 13.4 ± 7.9 months. During the follow-up period, 53 patients (20%) have died, 36 patients (13.6%) have undergone renal transplantation, 13 patients (4.9%) have switched off dialysis method and 5 patients (1.9%) have transferred to another facility. The cut-off of HGS able to predict mortality was 22.5 kg for men and 7 kg for women. Using this cut-off to fit the Kaplan–Meier survival curve, the association of HGS with all-cause mortality for both genders was confirmed. Finally, in the multivariate analysis adjusted for demographic, clinical and nutritional variables, HGS remained significant predictor of mortality, independent of dialysis modality. Conclusions: HGS cut-offs that predict mortality were 22.5 kg for men and 7 kg for women. HGS was associated with mortality independent of dialysis modality.